Electrophotographic photoreceptor and image forming apparatus including the same
By adding optimized dispersed silicone particles and polycarbonate resin with specific structures to the surface layer of the organic photoelectric induction device in the electro-optical image forming device, the surface wear and image flow problems are solved, and an efficient and low-cost image formation effect is achieved.
Patent Information
- Application Number
- JP2023180357
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-05-02
AI Technical Summary
The organic photoelectric induction devices in the existing electro-optical image forming equipment are prone to surface wear when in contact with the cleaning knife, and are prone to image flow problems in high temperature and high humidity environments, and are costly and difficult to popularize.
Silica particles are added to the surface layer of the photoinductive layer, and their dispersion state is optimized, using polycarbonate resin with a specific bisphenol structure as a binding agent, adjusting the structure and composition of the surface layer to improve wear resistance and image quality.
It achieves high wear resistance, maintains image sensitivity and high-quality image formation, while reducing production costs and is suitable for a wide range of applications.
Smart Images

Figure 2025070209000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrophotographic photoreceptor and an image forming apparatus including the same. [Background technology]
[0002] Electrophotographic image forming apparatuses that form images using electrophotographic technology are widely used in digital copiers, printers, facsimile machines, and the like. An electrophotographic photoreceptor (hereinafter also referred to as "photoreceptor") used in an electrophotographic process is constructed by laminating a photosensitive layer containing a photoconductive material on a conductive support (hereinafter also referred to as "conductive substrate"). Currently, research and development of photoreceptors having a photosensitive layer whose main component is an organic photoconductive material (also called "organic photoreceptors") is progressing, and they now account for the majority of photoreceptors in practical image forming devices. However, organic photoreceptors have a drawback in that their surfaces are easily worn away by contact with a cleaning blade or the like due to the nature of the organic materials used. In addition, with the recent increase in contact charging methods using roller charging and the trend toward longer life, smaller size and higher speed of image forming apparatuses, the organic photoreceptors are exposed to harsh conditions in which their surfaces are more susceptible to wear.
[0003] In response to the problem of wear on the photoreceptor surface, attempts have been made to improve wear resistance, for example by providing a surface protection layer using a curable high printing resistance resin. However, as the printing resistance of the photoreceptor layer increases and the photoreceptor surface becomes difficult to refresh, damage to peripheral members such as the cleaning blade increases, and the risk of image deterioration such as image deletion in high-temperature and high-humidity environments increases due to adhesion of discharge products. Furthermore, the formation of a surface protective layer complicates the production process, leading to increased costs for the photoreceptor itself, making it too expensive for use in widespread machines.
[0004] In a photoconductor that does not have a surface protective layer and has a charge transport layer as the outermost layer of the photosensitive layer, the charge transport layer wears out and reaches the end of its life. Therefore, in order to suppress this wear, a method has been proposed in which a binder resin with a structure that is resistant to mechanical fatigue is used. For example, JP 2018-063367 A (Patent Document 1) proposes a method for improving the printing durability of a photoreceptor by introducing a polycarbonate resin having a specific biphenyl structure as a binder resin into the charge transport layer, which is the outermost surface layer of the photoreceptor. However, the binder resin described in Patent Document 1 has problems in that it has poor adhesion to the charge generation layer, poor charge injection from the charge generation layer, and the residual potential is higher than when a normal polycarbonate resin is used.
[0005] Furthermore, JP 2021-086133 A (Patent Document 2), like Patent Document 1, proposes a method of improving abrasion resistance and oil crack resistance by introducing a polycarbonate resin having a specific biphenyl structure to the outermost surface of a photoreceptor and further adding silica particles. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2018-063367 A [Patent Document 2] Patent Publication No. 2021-086133 Summary of the Invention [Problem to be solved by the invention]
[0007] According to Patent Document 2, the addition of silica particles improves adhesion between photosensitive layers, and in the case of a laminated photosensitive layer, adhesion between the lower charge generating layer and the upper charge transport layer. However, the inventors have confirmed that such improvement in adhesion is greatly influenced by the dispersion state of the silica particles, and if the dispersion state is insufficient, the improvement in adhesion to the lower layer is insufficient, the residual potential increases due to repeated fatigue, and stable image characteristics cannot be obtained over the long term. Specifically, when silica particles having a number average primary particle diameter exceeding 50 nm are added to the outermost layer of the photosensitive layer, there is a significant adverse effect on the residual potential, whereas when silica particles having a small number average primary particle diameter are added, the effect of improving printing durability tends to decrease. That is, in the above-mentioned prior art, it was difficult to simultaneously achieve high abrasion resistance, maintenance of sensitivity characteristics, and formation of high-quality images by using a polycarbonate resin having a specific biphenyl structure and silica particles in the surface layer of the photosensitive layer.
[0008] Therefore, an object of the present disclosure is to provide an electrophotographic photoreceptor that can simultaneously achieve high wear resistance, maintenance of sensitivity characteristics, and high-quality image formation, and an image forming apparatus equipped with the same. [Means for solving the problem]
[0009] As a result of intensive research into solving the above-mentioned problems, the inventors have found that the above-mentioned problems can be solved by dispersing silica particles in the outermost layer of a photosensitive layer that uses a polycarbonate resin having a specific biphenyl structure as a binder resin and optimizing the dispersion state, and have thus completed the present invention.
[0010] Thus, according to the present disclosure, there is provided an electrophotographic photoreceptor having at least one photosensitive layer composed of one or more layers on a conductive support, the surface layer of the photosensitive layer contains a binder resin and silica particles; the silica particles have a number average primary particle diameter of 30 nm or less and are contained in an amount of 7 to 20 mass % relative to the total solid content of the surface layer; The binder resin is represented by the general formula (I) consisting of structural units (A) and (B): [ka]
[0011] (In the formula, R11, R12, R21 and R22 are the same or different and each is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms or a fluoroalkyl group having 1 to 3 carbon atoms; X is a phenylene group, a biphenylene group, a naphthylene group, an alkylene group having 1 to 3 carbon atoms or a cycloalkyl group having 3 to 6 carbon atoms.) an alkylene group, and m and n are indices that satisfy the relationship 0.3≦m / (n+m)≦0.55. It is a polycarbonate resin represented by the formula: a 4 mm-wide region at the center of a charged region in the axial direction of the electrophotographic photoreceptor on the surface of the surface layer of the photosensitive layer has an average spacing Sm of irregularities of 15 to 60 μm as defined in JIS-B-0601 (1994); The surface of the surface layer of the photosensitive layer has a contact angle with pure water of 85 to 94°. The electrophotographic photoreceptor is characterized in that
[0012] Furthermore, according to the present disclosure, there is provided an image forming apparatus comprising at least the above-mentioned electrophotographic photosensitive member, a charging means for charging the electrophotographic photosensitive member, an exposure means for exposing the charged electrophotographic photosensitive member to light to form an electrostatic latent image, a developing means for developing the electrostatic latent image to form a toner image, and a transfer means for transferring the toner image onto a recording medium. Effect of the Invention
[0013] According to the present disclosure, it is possible to provide an electrophotographic photoreceptor that can simultaneously achieve high wear resistance, maintenance of sensitivity characteristics, and high-quality image formation, and an image forming apparatus including the same. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic diagram showing the mechanism by which the incorporation of silica particles having a specific number average primary particle size improves the adhesion of the constituent layers of a photoreceptor, showing (a) a coating of a charge transport layer on a charge generation layer, and (b) the charge transport layer on the charge generation layer after heat treatment. [Diagram 2] FIG. 1 is a schematic diagram showing the mechanism by which the surface spacing of the irregularities in the surface layer of a photoreceptor, which reflects the dispersion state of silica particles, affects the adhesion of the constituent layers of the photoreceptor, in which (a) the surface spacing is good, (b) the surface spacing is poor, (c) the surface spacing is large, and (d) the surface spacing is small. [Diagram 3] FIG. 2 is a schematic diagram showing the adhesiveness of the constituent layers of the photoreceptor, (a) showing the state when dry, and (b) showing the state when the adhesiveness has decreased. [Figure 4] 1 is a schematic cross-sectional view showing the configuration of a main part of a photoreceptor 1 according to the present disclosure. [Diagram 5] 1 is a schematic side view showing a configuration of a main part of an image forming apparatus 100 according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The electrophotographic photoreceptor of the present disclosure is an electrophotographic photoreceptor including at least one photosensitive layer formed on a conductive support, the surface layer of the photosensitive layer contains a binder resin and silica particles; the silica particles have a number average primary particle diameter of 30 nm or less and are contained in an amount of 7 to 20 mass % relative to the total solid content of the surface layer; The binder resin is represented by the general formula (I) consisting of structural units (A) and (B): [ka]
[0016] (In the formula, R11, R12, R21, and R22 are the same or different and each is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a fluoroalkyl group having 1 to 3 carbon atoms; X is a phenylene group, a biphenylene group, a naphthylene group, an alkylene group having 1 to 3 carbon atoms, or a cycloalkylene group having 3 to 6 carbon atoms; and m and n are indexes that satisfy the relationship 0.3≦m / (n+m)≦0.55.) It is a polycarbonate resin represented by the formula: a 4 mm-wide region at the center of a charged region in the axial direction of the electrophotographic photoreceptor on the surface of the surface layer of the photosensitive layer has an average spacing Sm of irregularities of 15 to 60 μm as defined in JIS-B-0601 (1994); The surface of the surface layer of the photosensitive layer has a contact angle with pure water of 85 to 94°. It is characterized by: Below, the constituent features that characterize the photoreceptor of the present disclosure will be described, and then (1) the photoreceptor and (2) the image forming apparatus will be described. It should be noted that the embodiments and examples described below are merely specific examples of the present invention, and the present invention is not limited thereto.
[0017] <Silica particles> Examples of the silica particles contained in the surface layer of the photosensitive layer of the photoreceptor include dry silica particles and wet silica particles. Examples of dry silica particles include combustion silica (fumed silica) obtained by burning a silane compound, and deflagration silica obtained by explosively burning metallic silicon powder. Examples of wet silica particles include wet silica particles obtained by a neutralization reaction between sodium silicate and a mineral acid (precipitation method silica synthesized and agglomerated under alkaline conditions, gel method silica particles synthesized and agglomerated under acidic conditions), colloidal silica particles (silica sol particles) obtained by making acidic silicic acid alkaline and polymerizing it, and sol-gel method silica particles obtained by hydrolysis of an organic silane compound (e.g., alkoxysilane). Among these, from the viewpoint of suppressing image defects due to the generation of residual potential and other deterioration of electrical properties (suppressing deterioration of fine line reproducibility), combustion method silica particles having a low silanol group content on the surface and a low porosity structure are desirable as silica particles. Furthermore, when the silica particles are treated with dimethyldichlorosilane or hexamethyldisilazane, the best electrophotographic properties can be achieved.
[0018] <Number average primary particle size of silica particles> The present inventors have found that when the surface layer of the photosensitive layer of a photoreceptor contains silica particles (small-diameter silica) having a number-average primary particle diameter of 30 nm or less and these particles are maintained in a favorable dispersed state in the surface layer, in the case of a laminated photosensitive layer, the adhesion between the charge transport layer and the charge generation layer is improved, and as a result, an increase in Vr due to repeated electrical fatigue is suppressed. FIG. 1 is a schematic diagram showing the mechanism by which the incorporation of silica particles having a specific number average primary particle size improves the adhesion of the constituent layers of a photoreceptor. (a) shows the coating of the charge transport layer on the charge generation layer, and (b) shows the charge transport layer on the charge generation layer after heat treatment. By dispersing silica particles in the photosensitive layer with good dispersibility within the range of the present disclosure, the surface area of the silica particles is increased and the state in which intermolecular forces work is maintained. By adding silica particles to the coating liquid for the charge transport layer, the coating liquid becomes thixotropic, and when the coating liquid is applied onto the charge generation layer, the coating liquid penetrates into the gaps between the pigments on the surface of the charge generation layer (CGL) (Figure 1(a)). By heat treating this, the solvent evaporates and the resin hardens (Figure 1(b)). Here, it is presumed that if the silica particles are in the charge transport layer (CTL), the distance between the silica particles after evaporation becomes small, and the effect of intermolecular forces becomes large, so that the silica particles adhere to the charge generation layer and the adhesiveness is increased. It is presumed that the increased adhesiveness of the charge transport layer to the charge generation layer promotes the injection of holes from the generated carriers into the charge transport layer. The method for measuring the number average primary particle diameter will be specifically described in the Examples.
[0019] The silica particles contained in the surface layer of the photosensitive layer of the photoreceptor of the present disclosure have a number average primary particle diameter of 30 nm or less. The smaller the number average primary particle size of the silica particles, the better the adhesion but the less advantageous it is in terms of printing durability. On the other hand, the larger the number average primary particle size of the silica particles, the less advantageous it is in terms of adhesion and the less advantageous it is in terms of reducing residual potential. In particular, when the number average primary particle size of the silica particles exceeds 30 nm, the contribution of the interaction between the particles becomes small and the adhesive effect may decrease. The number average primary particle diameter of the silica particles is preferably 10 to 20 nm, more preferably 15 to 20 nm, and particularly preferably 16 nm, as in the silica particles used in the examples, in order to maintain the best balance of properties.
[0020] <Dispersion state of silica particles> The present inventors have also confirmed that the dispersion state of silica greatly contributes to adhesion to the underlying layer and printing durability. FIG. 2 is a schematic diagram showing the mechanism by which the surface spacing Sm of the concaves and convexes on the surface layer of the photoreceptor, which reflects the dispersion state of the silica particles, affects the adhesion of the constituent layers of the photoreceptor. (a) shows the case of a good dispersion state, (b) shows the case of poor dispersion, (c) shows the case of a large number average primary particle diameter of the silica particles, and (d) shows the case of a small number average primary particle diameter of the silica particles. 1A shows that the ten-point surface roughness Rz and the surface spacing Sm of the asperities of the surface layer are both small, indicating a good dispersion state. In (b), both Rz and Sm are large, indicating that the dispersion of silica particles in the surface layer is insufficient. (c) shows that the particle size of the silica particles is large, Sm is large, the contribution of the interaction between particles is small, and the adhesive effect is low. (d) shows that when the particle size of the silica particles is too small and the dispersibility is improved, the intermolecular forces become strong, Sm becomes small, and the improvement range of Vr becomes large, but the effect of printing durability decreases. As described above, the present inventors have confirmed that there is a correlation between the "average spacing between dispersed silica particles" and the "average spacing Sm between the projections and recesses on the surface of the photosensitive layer."
[0021] <Surface condition of the photosensitive layer> A 4 mm wide area at the center of the charged area in the axial direction of the electrophotographic photosensitive member on the surface of the surface layer of the photosensitive layer has an average spacing Sm of irregularities of 15 to 60 μm as defined in JIS-B-0601 (1994). When the dispersibility of the silica particles is optimized and the average spacing Sm of the dispersed silica particles is adjusted to be greater than 15 μm and equal to or less than 60 μm, a favorable tendency is observed. If the average spacing Sm of the irregularities is less than 15 μm, the intermolecular forces of the silica particles become too strong, the photosensitive layer loses flexibility, and the printing durability effect may decrease.On the other hand, if the average spacing Sm of the irregularities is more than 60 μm, the contribution of the interparticle interaction becomes small, and the effect on adhesion may decrease. The average spacing Sm between the projections and recesses is preferably 25 to 60 μm, and more preferably 35 to 55 μm.
[0022] It is also preferred that a 4 mm-wide region at the center of the charged region in the axial direction of the photoreceptor on the surface of the surface layer of the photosensitive layer has a ten-point mean roughness Rz of 0.10 to 0.30 μm as defined in JIS-B-0601 (1994), and that the ten-point mean roughness Rz and the average spacing Sm of the irregularities satisfy the relationship Rz×Sm / 2≦10. If the ten-point average roughness Rz is less than 0.10 μm, the silica content may be too low, resulting in insufficient adhesion to the underlying layer. On the other hand, if the ten-point average roughness Rz exceeds 0.30 μm, silica aggregates are often present, which may result in inconsistent adhesion to the underlying layer or reduced dispersion stability of the coating liquid itself. The ten-point average roughness Rz is preferably 0.15 to 0.30 μm, and more preferably 0.15 to 0.28 μm.
[0023] If Rz×Sm / 2 exceeds 10, the contribution to adhesion may decrease. The lower limit of Rz×Sm / 2 is about 2.5 in order to ensure adhesion, and Rz×Sm / 2 is preferably 3.0 to 5.0, and more preferably 2.5 to 3.5. The method for measuring the ten-point surface roughness Rz and the average spacing between projections and recesses Sm will be described in the Examples.
[0024] <Silica particle content> The silica particles are contained in a proportion of 7 to 20% by mass based on the total solid content of the surface layer. If the content of silica particles is less than 7% by mass based on the total solid content of the surface layer, the adhesion and printing durability may be insufficient, whereas if the content of silica particles is more than 20% by mass based on the total solid content of the surface layer, the risk of agglomeration increases, and problems such as blade damage caused by agglomerations may occur when the blade is used after long-term storage. The content of the silica particles is preferably 7 to 15 mass %, and more preferably 7 to 12 mass %.
[0025] <Contact angle of the photosensitive layer surface with pure water> The present inventors have also confirmed that the adhesiveness of the photosensitive layer is increased by using a coating solution for the photosensitive layer containing silica particles in combination with a binder resin incorporating a siloxane skeleton resin, a fluorine resin, or a substituent group, which reduces the surface tension. This is presumably because, in the case of a laminated photosensitive layer, the wettability of the coating solution for the charge transport layer to the charge generation layer is improved. On the other hand, the present inventors have confirmed that the contact angle of the photosensitive layer surface is increased and the lubricity is improved by reducing the surface tension of the coating liquid for the photosensitive layer. Although it is good that the adhesion is improved, if the initial contact angle with pure water is made too high in the photoreceptor of the present disclosure, a difference in lubricity occurs between the image forming area at the center of the photoreceptor and the non-image forming area at the end due to repeated electrical fatigue, and blade curling at the end is likely to occur. It has been confirmed that by adjusting the contact angle to about 85 to 94 degrees, blade curling is suppressed and stable function can be exhibited for a long period of time. In addition, if the contact angle of the surface of the surface layer of the photosensitive layer with pure water is made too low, the photoreceptor will have an increase in the adhesion of discharge products and the like overall, which will increase the friction coefficient with the blade and cause blade reversal even in the image forming area. Therefore, in the photoreceptor of the present disclosure, the surface of the surface layer of the photosensitive layer has a contact angle with pure water of 85 to 94°. The method for measuring the contact angle with pure water will be specifically described in the Examples.
[0026] <Creep value C of photosensitive layer> The surface layer of the photoreceptor of the present disclosure preferably has a creep value C of 4.0% or more, measured by applying a maximum load of 30 mN for 5 seconds using a Vickers square pyramid diamond indenter with an opposing angle of 136° in an environment of a temperature of 25°C and a relative humidity of 50%. Introducing silica particles into the photosensitive layer tends to reduce the flexibility of the photosensitive layer, decreasing the creep value C. If the creep value C of the surface of the photosensitive layer is less than 4.0%, the layer tends to become brittle against external mechanical fatigue. The upper limit of the creep value C is about 5.0%, and the creep value C is preferably 4.0 to 4.6%. The method for measuring the creep value C will be specifically explained in the Examples.
[0027] <Binder resin> The binder resin contained in the surface layer of the photosensitive layer of the photoreceptor of the present disclosure is represented by the general formula (I): [ka]
[0028] (In the formula, R11, R12, R21, and R22 are the same or different and each is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a fluoroalkyl group having 1 to 3 carbon atoms; X is a phenylene group, a biphenylene group, a naphthylene group, an alkylene group having 1 to 3 carbon atoms, or a cycloalkylene group having 3 to 6 carbon atoms; and m and n are indexes that satisfy the relationship 0.3≦m / (n+m)≦0.55.) It is a polycarbonate resin (also called "copolymer polycarbonate resin") represented by the formula:
[0029] The substituents and indices of general formula (I) will be described. Examples of the alkyl group having 1 to 3 carbon atoms for the substituents R11, R12, R21 and R22 include methyl, ethyl, n-propyl and isopropyl. Examples of the fluoroalkyl group having 1 to 3 carbon atoms for the substituents R11, R12, R21 and R22 include fluoromethyl, difluoromethyl and trifluoromethyl.
[0030] Examples of the alkylene group having 1 to 3 carbon atoms for the substituent X include methylene, ethylene, n-propylene, and isopropylene. Examples of the cycloalkylene group having 3 to 6 carbon atoms for the substituent X include cyclopropylene, isobutylene, isopentylene, and cyclohexylene.
[0031] If m / (n+m) is less than 0.3, the printing durability and electrical fatigue resistance may be insufficient, whereas if m / (n+m) is more than 0.55, there may be a problem with solubility, leading to poor productivity. The preferred relationship between m and n is 0.35≦m / (n+m)≦0.50.
[0032] In the photoreceptor of the present disclosure, the structural unit (A) of the polycarbonate resin is represented by the following formula: [ka]
[0033] (wherein R1 is a hydrogen atom, an alkyl group having 1 or 2 carbon atoms, or a fluoroalkyl group having 1 or 2 carbon atoms). A structural unit (A1) represented by the formula: It is preferable that the mass Bw of the binder resin in the surface layer of the photosensitive layer and the mass Hw of the low molecular weight component having a molecular weight of 1000 or less satisfy the relationship 38.2≦Hw / (Hw+Bw)×100≦43.0. The low molecular weight component having a molecular weight of 1000 or less means components other than the binder resin in the photosensitive layer (excluding silica particles, which are inorganic materials), and when the photosensitive layer, which is a preferred embodiment of the photoreceptor of the present disclosure, is a laminated type photosensitive layer, it means a charge transport material.
[0034] The inventors have confirmed that introducing the structural unit (A) into a polycarbonate resin improves the Vickers hardness of the photosensitive layer, thereby improving the mechanical strength of the photosensitive layer, and further that making the substituents on the aromatic rings of the structural unit (A) the same, as in the structural unit (A1), further improves the mechanical strength of the photosensitive layer.
[0035] If the relationship Hw / (Hw+Bw)×100 between the mass Bw of the binder resin and the mass Hw of the low molecular weight component with a molecular weight of 1000 or less is less than 38.2, the adhesion of the charge generating layer is insufficient, and the injection of charges from the charge generating layer tends to be poor. On the other hand, if Hw / (Hw+Bw)×100 exceeds 43.0, the printing durability becomes insufficient, and the advantages of the binder resin specified in the present disclosure may not be fully exhibited. This is presumably because, in the coating and formation of the photosensitive layer, the thermal contraction of the photosensitive layer is large when it dries (see FIG. 3(a)), and the internal stress becomes large (see FIG. 3(b)). More preferably, 39.0≦Hw / (Hw+Bw)×100≦43.0.
[0036] In the photoreceptor of the present disclosure, the structural unit (B) of the polycarbonate resin is represented by the following formula: [ka] or the structural unit (B1) represented by the following formula: [ka] It is preferable that the structural unit (B2) is represented by the following formula:
[0037] The present inventors have confirmed that damage caused by mechanical fatigue of the surface layer of the photosensitive layer can be reduced by introducing the structural unit (B1) into the structural unit (B) of the polycarbonate resin.
[0038] The present inventors have also confirmed that the resistance to electrical fatigue of the surface of the photosensitive layer can be improved by introducing the structural unit (B2) into the structural unit (B) of the polycarbonate resin. Polycarbonate resin is resistant to mechanical fatigue, and the surface of the photoconductor is difficult to refresh, and the surface lubricity of the image-forming area decreases, which tends to cause imbalance compared to the surface property of the non-image-forming area. Therefore, by introducing the structural unit (B2), it is possible to suppress the decrease in lubricity of the image-forming area. Although the structural unit (B2) has a lower mechanical strength of the photosensitive layer than the structural unit (B1), it has a higher resistance to electrical fatigue such as charging deterioration, can reduce friction with surrounding members, and can suppress wear of the photoconductor.
[0039] In a photoreceptor having a polycarbonate resin having the above structural unit, it is preferable that the substituents R11 and R12 of the structural unit (A) are hydrogen atoms, the structural unit (B) is the structural unit (B2), and the mass Bw of the binder resin in the surface layer of the photosensitive layer and the mass Hw of the low molecular weight component having a molecular weight of 1000 or less satisfy the relationship 34≦Hw / (Hw+Bw)×100≦41.
[0040] If the relationship Hw / (Hw+Bw)×100, which is the mass of the binder resin Bw and the mass Hw of the low molecular weight component with a molecular weight of 1000 or less, is less than 34, the adhesion to the charge generating layer is insufficient, and the injection of charges from the charge generating layer tends to be poor. On the other hand, if Hw / (Hw+Bw)×100 exceeds 43, the binder component in the photosensitive layer becomes too small, which tends to reduce resistance to charging fatigue. Therefore, when the relationship 34≦Hw / (Hw+Bw)×100≦41 is satisfied, good characteristics are obtained. More preferably, 35.0≦Hw / (Hw+Bw)×100≦38.5.
[0041] In the general formula (I) of the polycarbonate resin, it is preferred that R11 and R12 are the same substituent, R21 and R22 are the same substituent, and either one of R11 and R21 is a hydrogen atom. The present inventors have confirmed that when the paired substituents of the structural units (A) and (B) of the polycarbonate resin are the same, the mechanical strength, such as Vickers hardness, of the photosensitive layer is increased.
[0042] The polycarbonate resin of the binder resin of the photoreceptor of the present disclosure preferably has a chain end group consisting of a monovalent aromatic group, i.e., the chain end of the polycarbonate resin is preferably blocked with a monovalent aromatic group. The chain end group of the polycarbonate resin has the function of improving the lubricity of the surface of the photosensitive layer. In addition, the chain end group may be a monovalent fluorine-containing aliphatic group. In this case, even if the surface of the surface layer of the photoreceptor is scraped, the lubricity of the surface of the photosensitive layer can be controlled and blade reversal and the like can be suppressed because a certain amount of the fluorine-containing aliphatic groups of the chain end groups incorporated in the polycarbonate resin is present on the surface.
[0043] Examples of monovalent aromatic groups at the chain end groups include p-tert-butyl-phenonyl, p-phenylphenonyl, and p-cumylphenonyl. Examples of the monovalent fluorine-containing aliphatic group at the chain end include 2,2-difluoro-2-(perfluorohexyloxy)ethoxy and the following F1 to F4. Among these chain end groups, p-tert-butyl-phenonyl is preferred because the introduction of a fluorine-containing aliphatic group may result in an excessively high contact angle of the photosensitive layer surface with pure water. By selecting the chain end group, it becomes possible to control the lubricity of the surface of the photoreceptor, and the above chain end groups are preferred from the viewpoint of improving electrical properties and abrasion resistance.
[0044] [ka]
[0045] The polycarbonate resin having a specific structure contained in the photosensitive layer of the photoreceptor of the present disclosure can be synthesized by the method described in Japanese Patent No. 6,893,205, for example. The above chain end groups are derived from the end-capping agent used in the synthesis of the resin. Examples of the end-capping agent include monovalent carboxylic acids and derivatives thereof, and monovalent phenols. Specific examples include p-tert-butyl-phenol, p-phenylphenol, p-cumylphenol, 2,2-difluoro-2-(perfluorohexyloxy)ethanol, and fluorine-containing alcohols corresponding to the above (F1) to (F4).
[0046] Polycarbonate resins having a repeating unit represented by general formula (I) are listed below, but are not limited to these, and two or more of these resins can also be used in combination. Table 1 also shows the substituents and chain end groups of the compounds (1) to (11) of the polycarbonate resins exemplified therein.
[0047] [ka]
[0048] [ka]
[0049] [ka]
[0050] [Table 1]
[0051] <Viscosity average molecular weight of polycarbonate resin> The viscosity average molecular weight of the polycarbonate resin is preferably about 45,000 to 65,000. If the viscosity average molecular weight is less than 45,000, the printing durability may be insufficient, while if it exceeds 65,000, the viscosity of the coating liquid may become too high, increasing the risk of occurrence of coating defects during coating. The viscosity average molecular weight of the preferred polycarbonate resin is about 50,000 to 62,000.
[0052] (1) Electrophotographic Photoreceptor The photoreceptor of the present disclosure includes at least a photosensitive layer composed of one or more layers on a conductive support. Examples of the photosensitive layer include a laminated type photosensitive layer in which a charge generating layer containing a charge generating substance and a charge transport layer containing a charge transport substance are laminated in this order, and a single-layer type photosensitive layer containing a charge generating substance and a charge transport substance. In a single-layer photoreceptor having a single-layer photosensitive layer, the charge generating material is uniformly present in the photosensitive layer, so the electron travels a longer distance than in a laminated photoreceptor having a laminated photosensitive layer, and the laminated photoreceptor is more susceptible to the influence of a trapping material present in the photosensitive layer. When silica particles are contained in the photosensitive layer as in the photoreceptor of the present disclosure, the silica particles become traps, so that a laminated photoreceptor is preferred from the viewpoint of electrical properties. The photoreceptor of the present disclosure having a multi-layered photosensitive layer will be described below with reference to the drawings, but the present invention is not limited thereto.
[0053] FIG. 4 is a schematic cross-sectional view showing the configuration of a main part of the photoreceptor 1 of the present disclosure. The laminated photoreceptor 1 includes a photosensitive layer 15 in which an undercoat layer 12, a charge generating layer 13 containing a charge generating material, and a charge transport layer 14 containing a charge transport material and silica particles 16 are laminated in this order on a conductive support 11.
[0054] <Conductive support 11> The conductive support has a function as an electrode for the photoreceptor and a function as a support member, and the material constituting the conductive support is not particularly limited as long as it is a material used in the relevant technical field. Specific examples include metal materials such as aluminum, aluminum alloys, copper, zinc, stainless steel, and titanium, as well as polymer materials such as polyethylene terephthalate, nylon, and polystyrene, whose surfaces are laminated with metal foil, subjected to metal vapor deposition, or vapor-deposited or coated with a layer of a conductive compound such as a conductive polymer, tin oxide, or indium oxide, as well as hard paper and glass. Among these, aluminum is preferred from the viewpoint of ease of processing, and aluminum alloys such as JIS 3003, JIS 5000, and JIS 6000 are particularly preferred. The shape of the conductive support is not limited to a cylindrical shape (drum shape) as shown in FIG. 5, but may be a sheet shape, a columnar shape, an endless belt shape, or the like. In addition, the surface of the conductive support may be subjected to anodizing film treatment, surface treatment with chemicals or hot water, coloring treatment, or diffuse reflection treatment such as surface roughening, as necessary, to prevent interference fringes caused by laser light, within a range that does not affect image quality.
[0055] <Undercoat layer 11> The photoreceptor of the present disclosure preferably includes an undercoat layer (also called an "intermediate layer") between the conductive support and the photosensitive layer. The undercoat layer generally covers the unevenness of the surface of the conductive support to make it uniform, improves the film-forming property of the laminated photosensitive layer, suppresses peeling of the photosensitive layer from the conductive support, and improves the adhesion between the conductive support and the photosensitive layer. Specifically, it prevents the injection of electric charges from the conductive support into the photosensitive layer, prevents the chargeability of the photosensitive layer from decreasing, and prevents fogging of the image (so-called black spots). The undercoat layer can be formed, for example, by dissolving a binder resin in a suitable solvent to prepare a coating liquid for the undercoat layer, coating this coating liquid on the surface of the conductive support, and removing the organic solvent by drying.
[0056] Examples of the binder resin include acetal resin, polyamide resin, polyurethane resin, polyester resin, acrylic resin, epoxy resin, phenol resin, melamine resin, urethane resin, etc. The binder resin is required to have properties such as not dissolving or swelling in the solvent used when forming the photoconductor layer on the undercoat layer, excellent adhesion to the conductive support, and flexibility. Among the above binder resins, polyamide resin is preferred, and alcohol-soluble nylon resin and polyamide resin containing a piperazine compound are particularly preferred. Examples of alcohol-soluble nylon resins include homopolymer or copolymer nylons such as 6-nylon, 66-nylon, 610-nylon, 11-nylon, and 12-nylon, and chemically modified nylons such as N-alkoxymethyl modified nylons. A curing agent that crosslinks the binder resin may be used to form a cured film. As the curing agent, blocked isocyanate is preferred from the viewpoint of storage stability and electrical properties of the coating liquid.
[0057] Examples of the solvent include lower alcohols such as water, methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butanol, 2-butanol, and isobutanol, ketones such as acetone, cyclohexanone, and 2-butanone, ethers such as tetrahydrofuran, dioxane, ethylene glycol, and diethyl ether, and halogenated hydrocarbons such as methylene chloride and ethylene chloride. An appropriate solvent is selected from these solvents based on the solubility of the binder resin and the surface smoothness of the undercoat layer, and one type may be used alone or two or more types may be used in combination. Among these solvents, for example, non-halogenated organic solvents can be preferably used in consideration of the global environment.
[0058] The coating solution for the undercoat layer may contain metal oxide particles, which can easily adjust the volume resistivity of the undercoat layer, further suppress the injection of charges into the charge generating layer, and maintain the electrical properties of the photoreceptor under various environments. Materials that can be used for the metal oxide particles include, for example, titanium oxide, aluminum oxide, aluminum hydroxide, and tin oxide. In the coating liquid for forming an undercoat layer, the ratio (A / B) of the total mass A of the binder resin and metal oxide particles to the mass B of the solvent is, for example, preferably about 1 / 99 to 30 / 70, and particularly preferably about 2 / 98 to 40 / 60. The ratio (C / D) of the mass C of the binder resin to the mass D of the metal oxide particles is, for example, preferably about 1 / 99 to 90 / 10, and particularly preferably about 5 / 95 to 70 / 30.
[0059] The coating method for the undercoat layer coating liquid may be appropriately selected from among the most suitable methods taking into consideration the physical properties of the coating liquid and productivity, and examples of the method include spraying, bar coating, roll coating, blade coating, ring coating, and dip coating. Among these, the dip coating method is a method in which a conductive support is immersed in a coating tank filled with a coating liquid, and then pulled up at a constant speed or a gradually changing speed to form a layer on the surface of the conductive support, and is relatively simple and has excellent productivity and cost, so it can be suitably used for manufacturing photoreceptors. The device used for the dip coating method may be provided with a coating liquid dispersion device, typically an ultrasonic generator, in order to stabilize the dispersibility of the coating liquid.
[0060] The solvent in the coating film may be removed by natural drying, but the solvent in the coating film may also be removed forcibly by heating. The temperature in such a drying step is not particularly limited as long as it is a temperature at which the solvent used can be removed, but a temperature of about 50 to 140°C is appropriate, and a temperature of about 80 to 130°C is particularly preferable. If the drying temperature is less than 50°C, the drying time may be long and the solvent may not evaporate sufficiently and remain in the photoreceptor layer, while if the drying temperature exceeds about 140°C, the electrical characteristics of the photoreceptor may deteriorate during repeated use, resulting in poor quality of the obtained image. Such temperature conditions are common not only to the formation of the undercoat layer, but also to the formation of layers such as the photosensitive layer, which will be described later, and other treatments.
[0061] The thickness of the undercoat layer is not particularly limited, but is preferably 0.01 to 20 μm, and more preferably 0.05 to 10 μm. If the thickness of the undercoat layer is less than 0.01 μm, sufficient blocking effect against electron injection from the conductive support side and sufficient effect against interference fringes due to light scattering may not be obtained. On the other hand, if the thickness of the undercoat layer exceeds 20 μm, the change in sensitivity during continuous printing may become large, which may result in a large change in image density.
[0062] <Charge generating layer 15> The charge generation layer has the function of generating charges by absorbing light irradiated by a light emitting device such as a light beam from a semiconductor laser in an image forming device, etc., and contains a charge generation substance as its main component and, as necessary, a binder resin and / or additives. The charge generating material can be a compound used in the field, specifically, azo pigments such as monoazo pigments, bisazo pigments and trisazo pigments; indigo pigments such as indigo and thioindigo; perylene pigments such as peryleneimide and perylene acid anhydride; polycyclic quinone pigments such as anthraquinone and pyrenequinone; phthalocyanine pigments such as metal phthalocyanine and metal-free phthalocyanine such as titanyl phthalocyanine; organic photoconductive materials such as squarylium dyes, pyrylium salts, thiopyrylium salts, triphenylmethane dyes; and inorganic photoconductive materials such as selenium and amorphous silicon, and can be appropriately selected and used from those having sensitivity in the exposure wavelength range. These charge generating materials can be used alone or in combination of two or more. Among these charge generating materials, those represented by the following general formula (A):
[0063] [ka]
[0064] (In the formula, X 1 , X 2 , X 3 and X 4 are the same or different and each is a halogen atom, an alkyl group, or an alkoxy group, and r, s, y, and z are the same or different and each is an integer of 0 to 4. It is preferable to use titanyl phthalocyanine represented by the following formula: Titanyl phthalocyanine is a charge-generating material that has high charge generation efficiency and charge injection efficiency in the emission wavelength range (near-infrared light) of currently commonly used laser light and LED light. It generates a large amount of charge by absorbing light and can efficiently inject the generated charge into the hole-transporting material without accumulating it internally.
[0065] The titanyl phthalocyanine represented by the general formula (A) can be produced by known production methods such as the method described in Phthalocyanine Compounds by Moser, Frank H. and Arthur L. Thomas, Reinhold Publishing Corp., New York, 1963. For example, among the titanyl phthalocyanine compounds represented by the general formula (A), in the case of an unsubstituted titanyl phthalocyanine in which r, s, y, and z are 0, it can be obtained by synthesizing dichlorotitanyl phthalocyanine by heating and melting phthalonitrile and titanium tetrachloride or by heating and reacting them in a suitable solvent such as α-chloronaphthalene, and then hydrolyzing the resultant with a base or water. Alternatively, the titanyl phthalocyanine composition can be produced by reacting isoindoline with a titanium tetraalkoxide such as tetrabutoxytitanium under heating in a suitable solvent such as N-methylpyrrolidone.
[0066] The method for forming the charge generation layer includes a method of vacuum-depositing the charge generation material on the conductive support, and a method of dispersing the charge generation material in a solvent and applying a coating liquid for the charge generation layer onto the conductive support. Among these, a method of dispersing the charge generation material in a binder resin solution obtained by mixing a binder resin in a solvent by a conventionally known method and applying the coating liquid for the charge generation layer onto the conductive support is preferred. This method will be described below.
[0067] The binder resin is not particularly limited, and any resin known in the art can be used. Examples of the binder resin include polyester, polystyrene, polyurethane, phenolic resin, alkyd resin, melamine resin, epoxy resin, silicone resin, acrylic resin, methacrylic resin, polycarbonate, polyarylate, polyphenoxy, polyvinyl butyral, and polyvinyl formal resins, as well as copolymer resins containing two or more of the repeating units constituting these resins. Examples of the copolymer resin include insulating resins such as vinyl chloride-vinyl acetate copolymer resin, vinyl chloride-vinyl acetate-maleic anhydride copolymer resin, and acrylonitrile-styrene copolymer resin. These resins can be used alone or in combination of two or more.
[0068] Examples of the solvent include halogenated hydrocarbons such as dichloromethane and dichloroethane, ketones such as acetone, methyl ethyl ketone and cyclohexanone, esters such as ethyl acetate and butyl acetate, ethers such as tetrahydrofuran (THF) and dioxane, alkyl ethers of ethylene glycol such as 1,2-dimethoxyethane, aromatic hydrocarbons such as benzene, toluene and xylene, and aprotic polar solvents such as N,N-dimethylformamide and N,N-dimethylacetamide. These solvents can be used alone or in combination of two or more.
[0069] The compounding ratio between the charge generating substance and the binder resin is preferably such that the proportion of the charge generating substance is within a range of 10 to 99 mass %. If the ratio of the charge generating material is less than 10% by mass, the sensitivity may decrease. On the other hand, if the ratio of the charge generating material is more than 99% by mass, not only the film strength of the charge generating layer decreases, but also the dispersibility of the charge generating material decreases, the number of coarse particles increases, and the surface charge decreases in areas other than those that should be erased by exposure, resulting in image defects, particularly image fogging called black spots, in which toner adheres to a white background and tiny black spots are formed.
[0070] Before dispersing the charge generating material in the binder resin solution, the charge generating material may be pulverized in advance using a pulverizer such as a ball mill, a sand mill, an attritor, a vibration mill, or an ultrasonic disperser. Examples of dispersing machines used when dispersing the charge generating material in the binder resin solution include a paint shaker, a ball mill, a sand mill, etc. Appropriate dispersion conditions may be selected so as to prevent the incorporation of impurities due to wear of the container and members constituting the dispersing machine. The coating liquid for the charge generating layer may be applied by the same method as the coating liquid for the undercoat layer, and a dip coating method is particularly preferred.
[0071] The thickness of the charge generating layer is not particularly limited, but is preferably 0.05 to 5 μm, and more preferably 0.1 to 1 μm. If the thickness of the charge generating layer is less than 0.05 μm, the efficiency of light absorption decreases, and the sensitivity of the photoconductor may decrease. On the other hand, if the thickness of the charge generating layer exceeds 5 μm, the charge transfer inside the charge generating layer becomes the rate-limiting step in the process of erasing the charge on the surface of the laminated photosensitive layer, and the sensitivity of the photoconductor may decrease.
[0072] <Charge transport layer 16> The charge transport layer has the function of receiving the charge generated by the charge generating material and transporting it to the surface of the photoreceptor, and contains a charge transport material, a binder resin, silica particles, and additives as necessary. In the photoreceptor shown in Figure 4, the charge transport layer corresponds to the surface layer of the photoreceptor.
[0073] As the charge transport material, compounds used in the art can be used. Specific examples thereof include carbazole derivatives, pyrene derivatives, oxazole derivatives, oxadiazole derivatives, thiazole derivatives, thiadiazole derivatives, triazole derivatives, imidazole derivatives, imidazolone derivatives, imidazolidine derivatives, bisimidazolidine derivatives, styryl compounds, hydrazone compounds, polycyclic aromatic compounds, indole derivatives, pyrazoline derivatives, oxazolone derivatives, benzimidazole derivatives, quinazoline derivatives, benzofuran derivatives, acridine derivatives, phenazine derivatives, aminostilbene derivatives, triarylamine derivatives, triarylmethane derivatives, phenylenediamine derivatives, stilbene derivatives, butadiene derivatives, enamine derivatives, benzidine derivatives, polymers having groups derived from these compounds in the main chain or side chain (poly-N-vinylcarbazole, poly-1-vinylpyrene, ethylcarbazole-formaldehyde resin, triphenylmethane polymer, poly-9-vinylanthracene, etc.), and polysilanes. These hole transport materials can be used alone or in combination of two or more.
[0074] A preferred method for forming the charge transport layer is to disperse the charge transport material and silica particles in a binder resin solution obtained by mixing a binder resin in a solvent by a known method, and then coat the coating liquid for the charge transport layer on the charge generating layer. This method will be described below.
[0075] The charge transport layer may contain additives such as a plasticizer and a leveling agent, if necessary, in order to improve film-forming properties, flexibility and surface smoothness. Examples of the plasticizer include dibasic acid esters such as phthalic acid esters, fatty acid esters, phosphoric acid esters, chlorinated paraffin, epoxy type plasticizers, etc. Examples of the leveling agent include silicon-based leveling agents, etc.
[0076] Examples of the solvent include aromatic hydrocarbons such as benzene, toluene, xylene, and monochlorobenzene; halogenated hydrocarbons such as dichloromethane and dichloroethane; ethers such as THF, dioxane, and dimethoxymethyl ether; and aprotic polar solvents such as N,N-dimethylformamide. If necessary, solvents such as alcohols, acetonitrile, and methyl ethyl ketone can also be added. Among these solvents, non-halogenated organic solvents are preferably used in consideration of the global environment. These solvents may be used alone or in combination of two or more.
[0077] The compounding ratio of the charge transport material to the binder resin is preferably such that the proportion of the charge transport material is in the range of 30 to 43% by mass. If the ratio of the charge transport material is less than 30% by mass, the sensitivity characteristics may deteriorate and the resistance to repeated electrical fatigue may decrease, whereas if the ratio of the charge transport material is more than 43% by mass, the printing durability may be weakened and the photoreceptor life may be shortened. When the charge transport layer is the surface layer of the photosensitive layer, the content ratio of the silica particles to the total solid content of the surface layer is as described above.
[0078] The charge transport layer is formed, for example, in the same manner as in the case of forming the charge generation layer described above, by preparing a coating liquid for the charge transport layer by dissolving or dispersing a charge transport material, a binder resin, and, if necessary, the additives described above in an appropriate solvent, and applying this coating liquid onto the charge generation layer by a spray method, a bar coating method, a roll coating method, a blade method, a ring method, a dip coating method, etc. Among these coating methods, the dip coating method is particularly preferable in the case of forming the charge transport layer, since it is superior in various respects as described above.
[0079] The thickness of the charge transport layer is not particularly limited, but is preferably 5 μm to 50 μm, more preferably 10 μm to 40 μm. If the thickness of the charge transport layer is less than 5 μm, the charge retention ability of the photoreceptor surface may decrease. On the other hand, if the thickness of the charge transport layer is more than 50 μm, the resolution of the photoreceptor may decrease.
[0080] (2) Image forming apparatus 100 The image forming apparatus of the present disclosure is characterized by comprising at least the photoconductor of the present disclosure, a charging means for charging the photoconductor, an exposure means for exposing the charged photoconductor to light to form an electrostatic latent image, a developing means for developing the electrostatic latent image to form a toner image (make it visible), and a transfer means for transferring the toner image onto a recording medium. The image forming apparatus of the present disclosure may include a fixing means for fixing the transferred toner image onto a recording medium to form an image, a cleaning means for removing and recovering toner remaining on the photosensitive member, and a discharging means for discharging surface charges remaining on the photosensitive member. The image forming apparatus of the present disclosure and its operation will be described below with reference to the drawings, but the image forming apparatus of the present disclosure is not limited thereto.
[0081] FIG. 5 is a schematic side view showing the configuration of a main part of the image forming apparatus 100 of the present disclosure. The image forming apparatus (laser printer) 100 in Fig. 5 includes the photoreceptor 1 (corresponding to 1 in Fig. 4) of the present disclosure, an exposure means (semiconductor laser) 31, a charging means (charger) 32, a developing means (developer) 33, a transfer means (transfer charger) 34, a conveyor belt (not shown), a fixing means (fixer) 35, and a cleaning means (cleaner) 36. Reference numeral 51 denotes a recording medium (recording paper or transfer paper).
[0082] Photoconductor 1 is rotatably supported by the main body of image forming apparatus 100, and is driven to rotate around rotation axis 44 in the direction of arrow 41 by driving means (not shown). The driving means includes, for example, an electric motor and a reduction gear, and rotates photoconductor 1 at a predetermined peripheral speed by transmitting its driving force to a conductive support constituting the core body of photoconductor 1. Charging means 32, exposure means 31, developing means 33, transfer means 34, and cleaning means 36 are provided in this order along the outer circumferential surface of photoconductor 1 from the upstream side to the downstream side in the rotation direction of photoconductor 1 indicated by arrow 41.
[0083] The charger 32 is a charging means for uniformly charging the outer circumferential surface of the photoreceptor 1 to a predetermined potential. Examples of the charging means include a non-contact charging method such as a corona charging method using a charging device, and a contact charging method using a charging roller or a charging brush.
[0084] The exposure means 31 has a semiconductor laser as a light source, and irradiates the surface of the photoreceptor 1 between the charger 32 and the developer 33 with a laser beam light output from the light source, thereby exposing the charged outer peripheral surface of the photoreceptor 1 according to image information. The light is repeatedly scanned in the direction of extension of the rotation axis 44 of the photoreceptor 1, which is the main scanning direction, and these are focused to sequentially form electrostatic latent images on the surface of the photoreceptor 1. In other words, the charge amount of the photoreceptor 1, which has been uniformly charged by the charger 32, differs depending on whether it is irradiated with the laser beam or not, and an electrostatic latent image is formed.
[0085] The developing device 33 is a developing means that develops the electrostatic latent image formed on the surface of the photoconductor 1 by exposure with a developer (toner), and is provided facing the photoconductor 1. The developing device 33 includes a developing roller 33a that supplies toner to the outer peripheral surface of the photoconductor 1, and a casing 33b that rotatably supports the developing roller 33a about a rotation axis parallel to the rotation axis 44 of the photoconductor 1 and contains a developer including toner in its internal space.
[0086] The transfer charger 34 is a transfer means that transfers a toner image, which is a visible image formed on the outer peripheral surface of the photoconductor 1 by development, onto a transfer paper 51, which is a recording medium, supplied between the photoconductor 1 and the transfer charger 34 from the direction of the arrow 42 by a transport means (not shown). The transfer charger 34 is, for example, a contact type transfer means that includes a charging means and transfers the toner image onto the transfer paper 51 by applying a charge of the opposite polarity to that of the toner to the transfer paper 51.
[0087] The cleaner 36 is a cleaning means for removing and recovering the toner remaining on the outer peripheral surface of the photoreceptor 1 after the transfer operation by the transfer charger 34, and includes a cleaning blade 36a for removing the toner remaining on the outer peripheral surface of the photoreceptor 1, and a recovery casing 36b for containing the toner removed by the cleaning blade 36a. The cleaner 36 is also provided together with a static elimination lamp (not shown).
[0088] Furthermore, in the image forming apparatus 100, a fixing device 35, which is a fixing means for fixing a transferred image, is provided downstream of the conveyance of the transfer paper 51 that has passed between the photoconductor 1 and the transfer charger 34. The fixing device 35 includes a heating roller 35a having a heating means (not shown), and a pressure roller 35b that is provided opposite the heating roller 35a and is pressed against the heating roller 35a to form a contact portion. Reference numeral 37 denotes a separating means for separating the transfer paper from the photosensitive member, and reference numeral 38 denotes a housing for accommodating the various means of the image forming apparatus.
[0089] The image forming operation by this image forming apparatus 100 is carried out as follows. First, when the photoconductor 1 is rotated in the direction of arrow 41 by the driving means, the surface of the photoconductor 1 is uniformly charged to a predetermined positive potential by the charger 32, which is provided upstream of the image-forming point of the light by the exposure means 31 in the rotational direction of the photoconductor 1.
[0090] Next, light according to image information is irradiated from exposure means 32 onto the surface of photoreceptor 1. This exposure removes surface charge from the areas of photoreceptor 1 irradiated with light, creating a difference in surface potential between the areas irradiated with light and the areas not irradiated with light, forming an electrostatic latent image. Toner is supplied from a developing device 33, which is provided downstream in the rotational direction of the photoconductor 1 from the imaging point of the light by the exposure means 33, to the surface of the photoconductor 1 on which the electrostatic latent image is formed, thereby developing the electrostatic latent image and forming a toner image.
[0091] In synchronization with the exposure of the photoconductor 1, a transfer paper 51 is supplied between the photoconductor 1 and the transfer charger 34. The transfer charger 34 gives the supplied transfer paper 51 a charge of the opposite polarity to that of the toner, and the toner image formed on the surface of the photoconductor 1 is transferred onto the transfer paper 51. The transfer paper 51 onto which the toner image has been transferred is transported by the transport means to the fixing device 35, and is heated and pressurized as it passes through the contact area between the heating roller 35a and the pressure roller 35b of the fixing device 35, and the toner image is fixed onto the transfer paper 51 to form a robust image. The transfer paper 51 on which the image has been formed in this way is discharged to the outside of the image forming apparatus 100 by the transport means.
[0092] Meanwhile, the toner remaining on the surface of the photoreceptor 1 after the transfer of the toner image by the transfer charger 34 is peeled off from the surface of the photoreceptor 1 and collected by the cleaner 36. The charge on the surface of the photoreceptor 1 from which the toner has been removed in this manner is removed by light from a discharging lamp, and the electrostatic latent image on the surface of the photoreceptor 1 disappears. The photoreceptor 1 is then rotated again, and the series of operations starting with charging are repeated again to form images continuously.
[0093] The image forming apparatus 100 is a monochrome image forming apparatus (printer), but may be, for example, a color image forming apparatus of an intermediate transfer type capable of forming a color image. Specifically, it may be a so-called tandem type full-color image forming apparatus in which a plurality of electrophotographic photosensitive members on which toner images are respectively formed are arranged in a predetermined direction (for example, the horizontal direction H or the approximately horizontal direction H). The image forming apparatus 100 may also be another color image forming apparatus, a copying machine, a multifunction machine, or a facsimile machine. EXAMPLES
[0094] The present disclosure will be specifically described below with reference to examples and comparative examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present disclosure. In the examples and comparative examples, the materials used and the physical properties of the resulting photoreceptors were measured by the following methods.
[0095] (1) Number average primary particle size of silica particles Using a scanning electron microscope (SEM, Hitachi High-Technologies Corporation, model: S-4800), photograph the silica particles at a magnification of 30,000 to 300,000 times, for example, 100,000 times, and from the obtained image, 100 silica particles are arbitrarily observed as primary particles. The average particle size (major axis) in the Feret direction is calculated by image analysis, and this is defined as the number average primary particle size (nm).
[0096] (2) The ten-point average roughness Rz of the surface of the surface layer and the average spacing Sm of the surface irregularities of the surface layer Using a surface roughness measuring device (Tokyo Seimitsu Co., Ltd., model: Surfcom1400D), measure the ten-point surface roughness Rz (μm) and the average spacing Sm (μm) of the irregularities in a 4 mm wide area in the center of the axially charged area of the outermost surface layer (charge transport layer) of the photoconductor using a method with a reference length of 0.8 mm, a cutoff wavelength of 0.8 mm, a measurement speed of 0.1 mm / sec, and a Gaussian cutoff type. Calculate the ratio Sm / Rz from the results obtained. Rz and Sm correspond to the ten-point surface roughness Rz and the average spacing between projections and recesses Sm defined in JIS-B-0601 (1994).
[0097] (3) Contact angle of the photosensitive layer surface with pure water Using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., model: CA-X) and pure water as a reagent, the contact angle (°) of the charge transport layer surface before and after the durability test of the photoreceptor is measured.
[0098] (4) Creep value C of the photosensitive layer Using a microhardness tester (manufactured by Fischer Instruments, model: Fischerscope (registered trademark) H100V), a Vickers square pyramid diamond indenter with an opposing angle of 136° is used to apply a maximum load of 30 mN for 5 seconds in an environment of 25°C and 50% relative humidity to measure the creep value C (%). The creep value C (%) is calculated from the indentation depth h1 at the time when the maximum load of 30 mN is reached and the indentation depth h2 at the time when the maximum load of 30 mN is maintained, using the following formula. C(%)=100×(h2-h1) / h1
[0099] [Example 1] (Formation of Undercoat Layer) Three parts by weight of titanium oxide (manufactured by Ishihara Sangyo Kaisha, Ltd., product name: TYPAQUE (registered trademark) TTO-D-1) and two parts by weight of copolymer polyamide (nylon) (manufactured by Toray Industries, Inc., product name: AMILAN (registered trademark), grade: CM8000) were added to 25 parts by weight of methyl alcohol, and the mixture was dispersed for eight hours using a paint shaker to prepare 3 liters of coating solution for the undercoat layer. The obtained undercoat layer coating liquid was filled into a coating tank, and an aluminum drum-shaped support having a diameter of 30 mm and a length of 255 mm as the conductive support 11 was immersed in it and then removed. The obtained coating film was allowed to dry naturally, thereby forming an undercoat layer 12 with a thickness of 1 μm on the conductive support 11.
[0100] (Formation of Charge Generation Layer) Titanyl phthalocyanine represented by the following structural formula, which was to be used as a charge generating material, was prepared in advance. [ka]
[0101] 29.2 g of diiminoisoindoline and 200 ml of sulfolane were mixed, and 17.0 g of titanium tetraisopropoxide was added and reacted under a nitrogen atmosphere at 140° C. for 2 hours. The resulting reaction mixture was allowed to cool, and the precipitate was collected by filtration, washed successively with chloroform and a 2% aqueous hydrochloric acid solution, further washed successively with water and methanol, and dried to obtain 25.5 g of blue-purple crystals. As a result of chemical analysis of the obtained crystals, it was confirmed that they were titanyl phthalocyanine represented by the above structural formula (yield: 88.5%).
[0102] 1 part by weight of the obtained titanyl phthalocyanine and 1 part by weight of butyral resin (manufactured by Sekisui Chemical Co., Ltd., product name: S-LEC BM-2) were added to 98 parts by weight of methyl ethyl ketone, and the mixture was dispersed for 2 hours using a paint shaker to prepare 3 liters of a coating solution for the charge generating layer. The obtained coating liquid for the charge generating layer was applied onto the undercoat layer 12 by the same immersion method as in the case of forming the undercoat layer, and the obtained coating film was allowed to dry naturally to form a charge generating layer 13 with a thickness of 0.3 μm.
[0103] (Formation of charge transport layer) Next, 10 g of silica particles (manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R972, number average primary particle diameter 16 nm, dimethyldichlorosilane surface treatment) were suspended in 56.7 g of tetrahydrofuran and stirred for 5 minutes using a stirrer (manufactured by Yoshida Kikai Kogyo Co., Ltd., product name: Damatri System). The obtained suspension was transferred to a 500 mL wide-mouthed bottle, 33.3 g of tetrahydrofuran was added, and the mixture was stirred for 5 hours. 37.5 g of a stilbene derivative (compound (A)) represented by the following structural formula as a charge transport material, 52.5 g of a polycarbonate resin (compound (3), index m=3, n=7 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 61230) as a binder resin, 0.011 g of silicone oil (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KF96), and 386.2 g of tetrahydrofuran were added and mixed, and the mixture was stirred for another 10 hours.
[0104] [ka]
[0105] The resulting mixture was subjected to 10-pass dispersion processing in a wet media-less atomization device (manufactured by Yoshida Kikai Kogyo Co., Ltd., product name: Nanovater L-AS) to prepare a coating solution for the charge transport layer, and then a degassing process was performed for 3 minutes in a rotation-revolution type mixer (manufactured by Thinky Corporation, product name: Awatori Rentaro Atmospheric Type ARE-310) to obtain 536.0 g (yield 93.0%) of the coating solution for the charge transport layer.
[0106] The obtained coating liquid for the charge transport layer was applied onto the charge generation layer 13 by the same immersion method as in the case of forming the undercoat layer, and the obtained coating film was dried at 110°C for 1.0 hour and then dried at 130°C for 1 hour to form a surface layer (charge transport layer) 14 with a thickness of 35 μm, thereby obtaining the photoreceptor of Example 1 as shown diagrammatically in Figure 4. The compound (A) (stilbene compound) used was prepared in advance based on the method described in Japanese Patent No. 3272257.
[0107] [Example 2] In preparing the coating solution for forming the charge transport layer, 529.4 g (yield 91.8%) of the coating solution for the charge transport layer was obtained in the same manner as in Example 1, except that compound (3) (index m=4, n=6 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used as the polycarbonate resin, and the photoreceptor of Example 2 was obtained in the same manner as in Example 1.
[0108] [Example 3] In preparing the coating solution for forming the charge transport layer, 509.3 g (yield 88.4%) of the coating solution for the charge transport layer was obtained in the same manner as in Example 1, except that compound (3) (index m=5, n=5 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 62,830) was used as the polycarbonate resin, and the photoreceptor of Example 2 was obtained in the same manner as in Example 1.
[0109] [Example 4] In forming the charge transport layer, the photoconductor of Example 4 was obtained in the same manner as in Example 1, except that the silica particles were changed from 10 g to 7 g, and tetrahydrofuran was changed from 56.7 g to 39.7 g to prepare a suspension, the amount of tetrahydrofuran added to the wide-mouthed bottle was changed from 33.3 g to 23.3 g, the charge transport material compound (A) was changed from 37.5 g to 38.8 g, 54.3 g of compound (3) (index m=4, n=6 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used as the polycarbonate resin, and tetrahydrofuran was changed from 386.2 g to 413.7 g to obtain 537.0 g (yield 93.1%) of the coating liquid for the charge transport layer.
[0110] [Example 5] In forming the charge transport layer, the amount of silica particles was changed from 10g to 19g, and tetrahydrofuran from 56.7g to 107.7g to prepare a suspension, tetrahydrofuran was added to the wide-mouthed bottle from 33.3g to 63.3g, compound (A) as the charge transport material was changed from 37.5g to 33.8g, 47.3g of compound (3) (index m=4, n=6 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used as the polycarbonate resin, and tetrahydrofuran was changed from 386.2g to 305.7g to obtain 538.0g (yield 93.3%) of the coating liquid for the charge transport layer. The photoconductor of Example 5 was obtained in the same manner as in Example 1.
[0111] [Example 6] In forming the charge transport layer, 52.5 g of compound (3) (index m of general formula (I) = 5.5, n = 4.5, chain end group: p-tert-butylphenyl, viscosity average molecular weight 61200) was used as the polycarbonate resin, and 525.3 g (yield 91.2%) of the coating liquid for the charge transport layer was obtained without using silicone oil. The photoconductor of Example 6 was obtained in the same manner as in Example 1.
[0112] [Example 7] The photoreceptor of Example 7 was obtained in the same manner as in Example 1, except that in forming the charge transport layer, compound (10) (index m of general formula (I) = 5, n = 5, chain end group: 2,2-difluoro-2-(perfluorohexyloxy)ethoxy, viscosity average molecular weight 45020) was used as the polycarbonate resin, and 496.3 g of the coating solution for the charge transport layer was obtained (yield 94.5%).
[0113] [Example 8] In forming the charge transport layer, the charge transport material compound (A) was changed from 37.5 g to 32.1 g, 57.9 g of compound (3) (index m of general formula (I) = 4, n = 6, chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used as the polycarbonate resin, and 0.011 g of silicone oil was changed to 0.012 g to obtain 496.3 g (yield 94.5%) of the coating liquid for the charge transport layer. The photoconductor of Example 8 was obtained in the same manner as in Example 1, except that.
[0114] [Example 9] The photoreceptor of Example 9 was obtained in the same manner as in Example 1, except that in forming the charge transport layer, compound (8) (index m of general formula (I)=4, n=6, chain end group: p-tert-butylphenyl, viscosity average molecular weight: 59,862) was used as the polycarbonate resin to obtain 521.1 g (yield: 90.4%) of a coating solution for the charge transport layer.
[0115] [Example 10] The photoreceptor of Example 10 was obtained in the same manner as in Example 1, except that in forming the charge transport layer, compound (4) (index m of general formula (I)=4, n=6, chain end group: p-tert-butylphenyl, viscosity average molecular weight 60,824) was used as the polycarbonate resin to obtain 513.6 g (yield 89.1%) of the coating liquid for the charge transport layer.
[0116] [Example 11] In forming the charge transport layer, the charge transport material compound (A) was changed from 37.5 g to 39.1 g, 50.9 g of compound (3) (index m=4, n=6 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used as the polycarbonate resin, and 0.0011 g of silicone oil was changed to 0.010 g to obtain 496.3 g (yield 91.8%) of the coating liquid for the charge transport layer. The photoconductor of Example 11 was obtained in the same manner as in Example 1.
[0117] [Example 12] The photoreceptor of Example 12 was obtained in the same manner as in Example 1, except that in forming the charge transport layer, the charge transport material compound (A) was changed from 37.5 g to 34.6 g, and 55.4 g of compound (6) (indexes m=5, n=5 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 61942) was used as the polycarbonate resin to obtain 553.6 g (yield 91.9%) of the coating liquid for the charge transport layer.
[0118] [Example 13] The photoreceptor of Example 13 was obtained in the same manner as in Example 1, except that in forming the charge transport layer, the charge transport material compound (A) was changed from 37.5 g to 34.6 g, and 55.4 g of compound (5) (index m of general formula (I) = 5, n = 5, chain end group: p-tert-butylphenyl, viscosity average molecular weight 59600) was used as the polycarbonate resin to obtain 542.1 g (yield 94.0%) of the coating liquid for the charge transport layer.
[0119] [Example 14] In forming the charge transport layer, the charge transport material compound (A) was changed from 37.5 g to 30.5 g, 59.5 g of compound (6) (index m=5, n=5 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 61942) was used as the polycarbonate resin, and 0.011 g of silicone oil was changed to 0.012 g to obtain 553.2 g (yield 96.0%) of the coating liquid for the charge transport layer. The photoreceptor of Example 14 was obtained in the same manner as in Example 1, except that.
[0120] [Example 15] The photoreceptor of Example 15 was obtained in the same manner as in Example 1, except that in forming the charge transport layer, 52.5 g of compound (6) (index m=5, n=5 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 61942) was used as the polycarbonate resin to obtain 543.2 g (yield 94.2%) of the coating liquid for the charge transport layer.
[0121] [Example 16] The photoreceptor of Example 16 was obtained in the same manner as in Example 1, except that in forming the charge transport layer, silica particles (manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R976, number average primary particle diameter 7 nm, dimethyldichlorosilane surface treatment) were used, and compound (3) (index m of general formula (I) = 4, n = 6, chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used as the polycarbonate resin, and 486.1 g of coating liquid for the charge transport layer was obtained (yield 84.4%).
[0122] [Example 17] The photoreceptor of Example 17 was obtained in the same manner as in Example 1, except that in forming the charge transport layer, silica particles (manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) NAX50, number average primary particle diameter 30 nm, hexamethyldisilazane surface treatment) were used, and compound (3) (index m of general formula (I) = 4, n = 6, chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used as the polycarbonate resin, and 552.3 g (yield 95.9%) of the coating liquid for the charge transport layer was obtained.
[0123] [Example 18] In forming the charge transport layer, the silica particles were changed from 10 g to 14 g, the charge transport material compound (A) was changed from 37.5 g to 35.8 g, 50.2 g of compound (3) (index m=5, n=5 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 60,800) was used as the polycarbonate resin, and the mixture was stirred for 30 seconds with a stirrer to obtain 499.6 g (yield 86.7%) of the coating liquid for the charge transport layer. The photoreceptor of Example 18 was obtained in the same manner as in Example 1, except that the silica particles were changed from 10 g to 14 g, the charge transport material compound (A) was changed from 37.5 g to 35.8 g, and 50.2 g of compound (3) (index m=5, n=5 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 60,800) was used as the polycarbonate resin.
[0124] [Example 19] In the formation of the charge transport layer, 15 g of silica particles (manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R974, number average primary particle diameter 12 nm, dimethyldichlorodisilazane surface treatment) were used, 56.7 g of tetrahydrofuran was changed to 85.0 g to prepare a suspension, 33.3 g of tetrahydrofuran was changed to 50.0 g of tetrahydrofuran to be added to the wide-mouthed bottle, compound (3) (index m = 3, n = 7 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 42000) was used as the polycarbonate resin, and 386.2 g of tetrahydrofuran was changed to 365.0 g to obtain 576.4 g (yield 95.3%) of the coating liquid for the charge transport layer. A photoconductor of Example 19 was obtained in the same manner as in Example 1.
[0125] [Example 20] In forming the charge transport layer, a suspension was prepared using silica particles (manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) NAX50, number average primary particle diameter 30 nm, hexamethyldisilazane surface treatment), a polycarbonate resin compound (3) (general formula (I) index m = 5.5, n = 4.5, chain end group: p-tert-butylphenyl, viscosity average molecular weight 64800) was used, tetrahydrofuran was changed from 386.2 g to 367.1 g, and 20 passes of dispersion treatment were performed using a wet media-less atomizer to obtain 476.2 g (yield 86.0%) of the coating liquid for the charge transport layer. The photoconductor of Example 19 was obtained in the same manner as in Example 1.
[0126] [Example 21] The photoreceptor of Example 21 was obtained in the same manner as in Example 1, except that in forming the charge transport layer, compound (2) (index m=4, n=6 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 62,300) was used as the polycarbonate resin to obtain 550.0 g (yield 95.5%) of a coating solution for the charge transport layer.
[0127] [Example 22] The photoreceptor of Example 22 was obtained in the same manner as in Example 1, except that in the formation of the charge transport layer, the silica particles were changed from 10 g to 19 g, the charge transport material compound (A) was changed from 37.5 g to 33.8 g, and 47.3 g of compound (3) (index m of general formula (I) = 3, n = 7, chain end group: p-tert-butylphenyl, viscosity average molecular weight 42000) was used as the polycarbonate resin to obtain 523.8 g (yield 90.8%) of the coating liquid for the charge transport layer.
[0128] [Example 23] In forming the charge transport layer, 7 g of silica particles (manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R976, number average primary particle diameter 7 nm, dimethyldichlorosilane surface treatment) were used, and compound (3) (index m of general formula (I) = 4, n = 6, chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used as the polycarbonate resin to obtain 527.0 g (yield 94.3%) of the coating liquid for the charge transport layer. A photoconductor of Example 23 was obtained in the same manner as in Example 1, except that.
[0129] [Comparative Example 1] A photoreceptor of Comparative Example 1 was obtained in the same manner as in Example 1, except that in forming the charge transport layer, compound (3) (index m=1, n=9 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 59,400) was used as the polycarbonate resin to obtain 554.9 g (yield 96.3%) of a coating solution for the charge transport layer.
[0130] [Comparative Example 2] A photoreceptor of Comparative Example 2 was obtained in the same manner as in Example 1, except that in forming the charge transport layer, compound (3) (index m of general formula (I) = 5.6, n = 4.4, chain end group: p-tert-butylphenyl, viscosity average molecular weight 59942) was used as the polycarbonate resin to obtain 478.1 g (yield 83.0%) of a coating solution for the charge transport layer.
[0131] [Comparative Example 3] In forming the charge transport layer, silica particles were not used, the charge transport material compound (A) was changed from 37.5 g to 34.5 g, 65.5 g of compound (3) (index m of general formula (I) = 5.5, n = 4.5, chain end group: p-tert-butylphenyl, viscosity average molecular weight 61200) was used as the polycarbonate resin, silicone oil was changed from 0.011 g to 0.013 g, and tetrahydrofuran was changed from 386.2 g to 476.2 g, to obtain 568.1 g (yield 98.6%) of the coating liquid for the charge transport layer. A photoconductor of Comparative Example 3 was obtained in the same manner as in Example 1, except that.
[0132] [Comparative Example 4] A photoreceptor of Comparative Example 4 was obtained in the same manner as in Example 1, except that in forming the charge transport layer, silica particles (manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) VPRY40S, number average primary particle diameter 80 to 100 nm, dimethyldichlorodisilazane surface treatment) were used, and compound (3) (index m of general formula (I) = 4, n = 6, chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used as the polycarbonate resin, and 553.5 g (yield 96.0%) of a coating liquid for the charge transport layer was obtained.
[0133] [Comparative Example 5] In the formation of the charge transport layer, the suspension was prepared by changing the amount of silica particles from 10g to 5g, and tetrahydrofuran from 56.7g to 28.3g, the amount of tetrahydrofuran added to the wide-mouthed bottle was changed from 33.3g to 16.7g, the charge transport material compound (A) was changed from 37.5g to 39.6g, 55.4g of compound (3) (general formula (I) index m = 4, n = 6, chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used as the polycarbonate resin, compound (3) (general formula (I) index m = 4, n = 6, chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used as the polycarbonate resin, and 386.2g of tetrahydrofuran was changed to 431.2g to obtain 556.2g (yield 96.5%) of the charge transport layer coating liquid. A photoconductor of Comparative Example 5 was obtained in the same manner as in Example 1.
[0134] [Comparative Example 6] In forming the charge transport layer, the photoconductor of Comparative Example 6 was obtained in the same manner as in Example 1, except that the silica particles were changed from 10 g to 21 g, and the tetrahydrofuran was changed from 56.7 g to 119.0 g to prepare a suspension, the amount of tetrahydrofuran added to the wide-mouthed bottle was changed from 33.3 g to 70.0 g, the charge transport material compound (A) was changed from 37.5 g to 32.9 g, 46.1 g of compound (3) (index m=4, n=6 in general formula (I), chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used as the polycarbonate resin, 0.011 g of silicone oil was changed to 0.009 g, and 386.2 g of tetrahydrofuran was changed to 287.2 g to obtain 482.3 g (yield 83.7%) of the coating liquid for the charge transport layer.
[0135] [Comparative Example 7] In forming the charge transport layer, 19 g of silica particles (manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R976, number average primary particle diameter 7 nm, dimethyldichlorosilane surface treatment) were used, 56.7 g of tetrahydrofuran was changed to 107.7 g to prepare a suspension, 33.3 g of tetrahydrofuran was changed to 63.3 g, 37.5 g of the charge transport material compound (A) was changed to 33.8 g, and polycarbonate resin was used. A photoconductor of Comparative Example 7 was obtained in the same manner as in Example 1, except that 47.3 g of compound (3) (index m of general formula (I)=4, n=6, chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used, 0.011 g of silicone oil was changed to 0.009 g, and 386.2 g of tetrahydrofuran was changed to 305.7 g, and 12 passes of dispersion treatment were performed using a wet media-less atomizer to obtain 470.4 g of a coating solution for a charge transport layer (yield 81.6%).
[0136] [Comparative Example 8] In the formation of the charge transport layer, 7 g of silica particles (manufactured by Nippon Aerosil Co., Ltd., trade name: AEROSIL (registered trademark) NAX50, number average primary particle diameter 30 nm, hexamethyldisilazane surface treatment) were used, 56.7 g of tetrahydrofuran was changed to 39.7 g to prepare a suspension, 33.3 g of tetrahydrofuran was added to the wide-mouthed bottle container was changed to 23.3 g, 37.5 g of the charge transport material compound (A) was changed to 38.8 g, 54.3 g of the polycarbonate resin compound (3) (general formula (I) index m = 4, n = 6, chain end group: p-tert-butylphenyl, viscosity average molecular weight 61156) was used, 386.2 g of tetrahydrofuran was changed to 413.7 g, and 553.2 g of the charge transport layer coating liquid (yield 95.9%) was obtained in the same manner as in Example 1 to obtain a photoreceptor of Comparative Example 8.
[0137] [Comparative Example 9] In forming the charge transport layer, the charge transport material compound (A) was changed from 37.5 g to 38.8 g, 54.3 g of polycarbonate resin compound (1) (index m of general formula (I) = 5.5, n = 4.5, chain end group: p-tert-butylphenyl, viscosity average molecular weight 62540) was used, and tetrahydrofuran was changed from 386.2 g to 401.0 g to obtain 562.3 g (yield 94.7%) of the coating liquid for the charge transport layer. A photoreceptor of Comparative Example 9 was obtained in the same manner as in Example 1, except that.
[0138] [Comparative Example 10] In forming the charge transport layer, 521.0 g (yield 90.4%) of a coating solution for the charge transport layer was obtained in the same manner as in Example 1, except that 52.5 g of compound (11) (index m=3, n=7 in general formula (I), chain end group: F1, viscosity average molecular weight 62500) was used as a polycarbonate resin. A photoreceptor of Comparative Example 10 was obtained in the same manner as in Example 1.
[0139] [evaluation] The photoreceptors prepared in Examples 1 to 22 and Comparative Examples 1 to 10 were evaluated for (1) printing durability, (2) sensitivity characteristics, (3) adhesion, and (4) blade curling as follows, and an overall evaluation was made based on these results.
[0140] (1) Printing durability The photoconductor to be evaluated was attached to the unit of a digital copier (model: BP-40C26, manufactured by Sharp Corporation) that had been modified for testing, and a developing unit was attached. The pressure at which the cleaning blade of the cleaning means contacted the photoconductor, the so-called cleaning blade pressure, was set to 21 gf / cm (2.05 × 10 -1 A printing durability test was conducted by printing a character test chart (ISO19752) on 300,000 sheets of recording paper in an environment of 35°C temperature and 85% relative humidity. The thickness of the photosensitive layer at the start of the printing durability test and after 300,000 images were formed was measured using a film thickness measuring device (Filmetrics Inc., Model: F-20-EXR). The amount of film loss per 100,000 rotations of the photosensitive drum was calculated from the difference between the film thickness at the start of the printing test and the film thickness after 300,000 images were formed. The printing durability was evaluated based on the amount of film loss obtained according to the following criteria. The greater the amount of film loss, the worse the printing durability was evaluated to be.
[0141] <Evaluation criteria> VG: Film loss <0.70μm / 100,000 revolutions Can be used without problems in multifunction devices or printers that require a long lifespan G: 0.70μm / 100,000 revolutions≦film loss amount<1.00μm / 100,000 revolutions Although the amount of film loss is somewhat large, it can be used without any problems except for multifunction machines and printers that require a long life. NB: 1.00μm / 100,000 revolutions≦film loss amount<1.50μm / 100,000 revolutions Although there is a large amount of film loss, it can be used without problems on inexpensive multifunction devices and printers. B: 1.50μm / 100,000 revolutions or less film loss There is a lot of film loss, which is problematic for practical use.
[0142] (2) Sensitivity characteristics The photoconductor to be evaluated was attached to the unit of a digital copier (Model: BP-40C26, manufactured by Sharp Corporation) that had been modified for testing, the developer was removed from the digital copier, and a surface potential meter (Model: MODEL 344, manufactured by Trek Japan) was attached to the development site instead. In an environment of 35°C temperature and 85% relative humidity, the initial residual potential and the surface potential of the photoconductor after electrical fatigue were measured, and the difference between these, ΔVr (V), was used to evaluate the sensitivity stability based on the following evaluation criteria and was used as an index of sensitivity deterioration due to repeated use.
[0143] <Evaluation criteria> VG:ΔVr<40 Can be used without problems in high-speed multifunction machines or printers that require high sensitivity G: 40≦ΔVr<80 Can be used without problems on low to medium speed multifunction devices or printers NB:80≦ΔVr<140 If you have a slow, inexpensive multifunction device or printer, the density may be a little low, but it can be used without any problems. B:140≦ΔVr Poor sensitivity, low concentration, and problematic for practical use
[0144] (3) Adhesiveness The surface of the photoreceptor (drum) to be evaluated was scratched with a cutter knife in a checkerboard pattern with a pitch of 1 mm on each side of 10 mm. Then, adhesive tape (manufactured by Nichiban Co., Ltd., product name: Nichiban Cellotape (registered trademark)) was applied to the scratches, and the adhesive tape was instantly peeled off to evaluate the adhesion of the photoreceptor according to the following criteria.
[0145] <Evaluation criteria> VG: The area of the missing part is within 5% of the total square area Can be used without problems in high-speed multifunction devices or printers that require high sensitivity G: The width of the peeling in the cut is wider than 4 points, and the area of the missing part is more than 5% but less than 35% of the total square area Can be used without problems on low to medium speed multifunction devices or printers NB: The width of the peeling in the cut is wider than 4 points, and the area of the missing part is 35% to 65% of the total square area. Although the density is slightly low, it can be used without problems on slow, inexpensive multifunction machines or printers. B: The area of the defect due to peeling is 65% or more of the total square area Poor sensitivity, low concentration, and problematic for practical use
[0146] (4) Blade curl The photoconductor to be evaluated was attached to the unit of a digital copier (model: MX-M3531, manufactured by Sharp Corporation) that had been modified for the test, and a durability test (printing test) was performed by printing (printing) a character test chart (ISO19752) on 80K sheets of recording paper in an environment of 35°C temperature / 80% relative humidity (normal temperature / normal humidity), and the resistance to blade reversal (resistance to blade curling) was evaluated. If blade reversal occurred after printing 30K or 60K sheets, the test was stopped at that point.
[0147] <Evaluation criteria> VG: No blade curling occurred after printing 80K sheets Extremely good resistance to blade curling G: The blade does not reverse after 60K sheets are printed, but it reverses by 80K sheets. Good resistance to blade curling NB: The blade did not reverse after 30,000 sheets were printed, but it started to reverse by 60,000 sheets. Level that does not pose a problem in practical use B: Blade reversal occurs after printing 30K sheets. Situations where there is a risk of using it for long life
[0148] (5) Overall evaluation Based on the above evaluation results, an overall evaluation was made according to the following criteria. <Evaluation criteria> VG: VG rating in all categories, very good condition Can be used without problems in multifunction machines or printers that require long life and high image quality G: Some items may have a G rating, but all items are rated G or higher Can be used without problems in any device other than multifunction devices or printers that require long life and high image quality. NB: Some items have an NB rating, but all items have an NB rating or higher If it is an inexpensive multifunction device or printer, it can be used without any problems. B: Any item has a B rating and cannot be used. Poor sensitivity, low concentration, and problematic for practical use
[0149] The main constituent materials of the surface layer (charge transport layer) of the photoreceptor and their physical properties as well as the surface properties of the surface layer are shown in Tables 2 and 3, and the evaluation results of the photoreceptor are shown in Tables 4 and 5. In Tables 2 and 3, the abbreviations for the chain end groups of the binder resins have the following meanings. ptBP: p-tert-butylphenyl FOEt: 2,2-difluoro-2-(perfluorohexyloxy)ethoxy F1: Fluorine-containing aliphatic group F1
[0150] [Table 2]
[0151] [Table 3]
[0152] [Table 4]
[0153] [Table 5]
[0154] The following can be seen from Tables 2 to 5: The photoreceptors of Examples 1 to 23, which satisfy the constituent requirements of the present disclosure, are excellent in terms of printing durability, increase in residual potential due to repeated fatigue, adhesion, and blade curling, whereas the photoreceptors of Comparative Examples 1 to 10, which do not satisfy the constituent requirements of the present disclosure, are inferior. These differences are presumably due to insufficient dispersion of silica particles in the photosensitive layer of the photoreceptor, problems with the structure of the binder resin, and changes in surface lubricity in the axial direction of the photoreceptor due to repeated use. In other words, the photoreceptor of the present disclosure is believed to be able to maintain high printing durability while improving adhesion between the constituent layers of the photoreceptor, particularly between the lower charge generating layer and the upper charge transport layer in the case of a laminated photoreceptor layer, and suppressing an increase in residual potential and blade curling, thereby obtaining stable image characteristics over a long period of time.
[0155] It can be seen that an increase in the content of silica particles in the photosensitive layer suppresses the adhesion of the photosensitive layer and the increase in Vr due to repeated use (Examples 2 and 4, and Comparative Example 3). When the structural unit (A) of the general formula (I) of the polycarbonate resin is the structural unit (A1) and the silica content is the same, it can be seen that a photoreceptor in which the mass Bw of the binder resin in the surface layer of the photosensitive layer and the mass Hw of the low molecular weight component with a molecular weight of 1000 or less satisfy the relationship 38.2≦Hw / (Hw+Bw)×100≦43.0 maintains printing durability while suppressing the adhesion of the photosensitive layer and the increase in Vr due to repeated use (Examples 2, 4, and 8). It can be seen that as the value of the above relational expression (3) increases, that is, as the content of the binder resin in the surface layer of the photosensitive layer decreases, the adhesiveness deteriorates (Example 11). It can be seen that as the value of the above relational expression (3) becomes smaller, the adverse effect of the increase in residual potential becomes greater (Example 8).
[0156] It can be seen that a photoreceptor (Example 2) in which the substituents R11 and R12, and R21 and R22 in the general formula (I) of the polycarbonate resin are the same substituents, and either R11 or R12, or R21 or R22 is a hydrogen atom, has superior printing durability compared to photoreceptors (Examples 9 and 10) that do not satisfy this condition. Further, in the above (6), it can be seen that a photoreceptor in which the structural unit (B) of the general formula (I) of the polycarbonate resin is the structural unit (B1) has an advantage in terms of printing durability compared to a photoreceptor (Example 21) that does not satisfy this condition.
[0157] When comparing a photoreceptor in which the structural unit (B) of the general formula (I) of the polycarbonate resin is structural unit (B1) (Example 3) with a photoreceptor in which the structural unit (B1) is (B2) (Examples 12 to 15), it is found that the former is superior in terms of printing durability and mechanical fatigue, while the latter is superior in terms of preventing blade curling and also tends to be favorable against electrical fatigue. This is presumably because the imbalance in lubrication in the axial direction of the latter photoconductor was improved compared to the former photoconductor, suppressing blade reversal. In addition, with regard to Hw / (Hw+Bw)×100, it is the same as described in (3) above, but since the structural unit (B2) of general formula (I) of the polycarbonate resin of the latter photoreceptor is weak against mechanical fatigue, it can be seen that setting the ratio lower overall provides a better balance of characteristics.
[0158] It can be seen that the photoreceptor having a large number average primary particle diameter of silica particles (Example 17) tends to have good printing durability, while the photoreceptor having a small number average primary particle diameter (Example 16) tends to have good adhesion and sensitivity characteristics, and the photoreceptor having a number average primary particle diameter of 10 to 20 nm (Example 2) tends to have a good balance between both properties.
[0159] In comparison with photoreceptors (Examples 1 to 3) in which the ten-point mean roughness Rz of the surface layer of the photoreceptor is 0.10 to 0.30 μm and the ten-point mean roughness Rz and the mean spacing Sm of the irregularities satisfy the relationship Rz×Sm / 2≦10, photoreceptors (Examples 18 to 20) in which Rz exceeds 0.30 μm have more silica-caused protrusions on the surface of the photosensitive layer, and the irregularities become increasingly larger due to repeated fatigue, making it easier for imbalances in lubrication in the axial direction of the photosensitive layer to occur and increasing the risk of blade reversal, and in particular, when the above-mentioned Rz×Sm / 2 exceeds 10 and becomes large, the dispersion state of the silica in the photosensitive layer tends to deteriorate and adhesion tends to decrease (Example 20).
[0160] A photoreceptor in which the chain end group of the polycarbonate resin general formula (I) is a monovalent fluorine-containing aliphatic group (Example 7) has good adhesion to the lower layer of the photosensitive layer and suppresses an increase in residual potential, as compared with a photoreceptor in which the chain end group is a monovalent aromatic group (Example 3). However, since the contact angle of the surface of the photosensitive layer with pure water is high, an imbalance in the axial direction is likely to occur in the lubrication of the photoreceptor surface after long-term use, which is unfavorable for blade curling. However, it is clear that this is effective in cases where the photoreceptor life is set short.
[0161] When the content of silica particles in the photosensitive layer is less than 7% by mass, the printing durability tends to be slightly inferior, and there is a tendency for the surface of the photosensitive layer to become more scratched after 100,000 rotations, which shows that the solvent crack resistance after the printing durability test is reduced (Comparative Example 5). On the other hand, when the content of silica particles in the photosensitive layer exceeds 20%, there is a tendency for printing durability to improve, and it is understood that, since chemically deteriorated products adhere to the surface of the photosensitive layer and the surface of the photosensitive layer is difficult to refresh, the binder resin is cut due to mechanical and electrical fatigue of the photosensitive layer, polar groups of the resin skeleton appear on the surface, and the wettability of the surface of the photosensitive layer decreases, thereby deteriorating the solvent crack resistance and light fastness (Comparative Example 6). [Explanation of symbols]
[0162] 1. Electrophotographic photoreceptor 11 Conductive support (conductive substrate) 12 Undercoat layer (middle layer) 13 Charge generation layer 14 Charge transport layer 14' Charge transport layer coating layer 15 Photosensitive layer (laminated photosensitive layer) 16 Silica particles
[0163] 31 Exposure means (semiconductor laser) 32 Charging means (charger) 33 Developing means (developer) 33a Developing roller 33b Casing 34 Transfer means (transfer charger) 35 Fixing means (fixing device) 35a Heating roller 35b Pressure roller 36 Cleaning means (cleaner) 36a cleaning blade 36b Recovery casing 37 Separation means 38 Housing 41, 42 arrow mark 44 Rotation axis 51 Recording media (recording paper or transfer paper) 100 Image forming apparatus (laser printer)
Claims
1. An electrophotographic photoreceptor comprising at least one photosensitive layer formed of one or more layers on a conductive support, the surface layer of the photosensitive layer contains a binder resin and silica particles; the silica particles have a number average primary particle diameter of 30 nm or less and are contained in an amount of 7 to 20 mass % based on the total solid content of the surface layer; The binder resin is represented by the general formula (I) consisting of structural units (A) and (B): 【Chemistry 1】 (In the formula, R11, R12, R21, and R22 are the same or different and each is a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a fluoroalkyl group having 1 to 3 carbon atoms; X is a phenylene group, a biphenylene group, a naphthylene group, an alkylene group having 1 to 3 carbon atoms, or a cycloalkylene group having 3 to 6 carbon atoms; and m and n are indexes that satisfy the relationship 0.3≦m / (n+m)≦0.55.) It is a polycarbonate resin represented by the formula: a 4 mm-wide region at the center of a charged region in the axial direction of the electrophotographic photoreceptor on the surface of the surface layer of the photosensitive layer has an average spacing Sm of irregularities of 15 to 60 μm as defined in JIS-B-0601 (1994); The surface of the surface layer of the photosensitive layer has a contact angle with pure water of 85 to 94°.
1. An electrophotographic photoreceptor comprising:
2. The structural unit (A) of the polycarbonate resin is represented by the following formula: 【Chemistry 2】 (wherein R1 is a hydrogen atom, an alkyl group having 1 or 2 carbon atoms, or a fluoroalkyl group having 1 or 2 carbon atoms). The structural unit (A1) is represented by the following formula:
2. The electrophotographic photoreceptor according to claim 1, wherein a mass Bw of the binder resin in the surface layer of the photosensitive layer and a mass Hw of a low molecular weight component having a molecular weight of 1000 or less satisfy the relationship: 38.2≦Hw / (Hw+Bw)×100≦43.
0.
3. The structural unit (B) of the polycarbonate resin is represented by the following formula: 【Chemistry 3】 or the structural unit (B1) represented by the following formula: 【Chemistry 4】 3. The electrophotographic photoreceptor according to claim 1, wherein the structural unit (B2) is represented by the following formula:
4. In the polycarbonate resin, the substituents R and R of the structural unit (A) are hydrogen atoms, and the structural unit (B) is the structural unit (B2), 4. The electrophotographic photoreceptor according to claim 3, wherein a weight Bw of the binder resin in the surface layer of the photosensitive layer and a weight Hw of a low molecular weight component having a molecular weight of 1000 or less satisfy the relationship: 34.ltoreq.Hw / (Hw+Bw).times.100.ltoreq.
41.
5. 3. The electrophotographic photoreceptor according to claim 1, wherein, in the general formula (I) of said polycarbonate resin, R11 and R12 are the same substituent, R21 and R22 are the same substituent, and either one of R11 and R21 is a hydrogen atom.
6. 3. The electrophotographic photoreceptor according to claim 1, wherein the silica particles have a number average primary particle size of 10 to 20 nm.
7. 3. The electrophotographic photoreceptor according to claim 1, wherein a 4 mm-wide region at a center of a charged region in an axial direction of the electrophotographic photoreceptor on the surface of the surface layer of the photosensitive layer has a ten-point mean roughness Rz of 0.10 to 0.30 μm as defined in JIS-B-0601 (1994), and the ten-point mean roughness Rz and an average interval Sm of the irregularities satisfy a relationship of Rz×Sm / 2≦10.
8. 3. The electrophotographic photoreceptor according to claim 1, wherein the polycarbonate resin has a chain end group consisting of a monovalent aromatic group.
9. 3. The electrophotographic photoreceptor according to claim 1, wherein the surface layer of the photosensitive layer has a creep value C of 4.0% or more, as measured by applying a maximum indentation load of 30 mN for 5 seconds using a Vickers square pyramid diamond indenter having an opposing angle of 136° in an environment of a temperature of 25° C. and a relative humidity of 50%.
10. 3. An image forming apparatus comprising at least the electrophotographic photoreceptor according to claim 1 or 2, a charging unit which charges the electrophotographic photoreceptor, an exposure unit which exposes the charged electrophotographic photoreceptor to light to form an electrostatic latent image, a developing unit which develops the electrostatic latent image to form a toner image, and a transfer unit which transfers the toner image onto a recording medium.
Citation Information
Patent Citations
Electrophotographic photoreceptor, process cartridge, and image forming apparatus
JP2018063367A
Image forming apparatus and image forming method
JP2021086133A